Pengaruh Oral Hygiene Dengan NaCL 0,9% Terhadap Penurunan Grade Mukositis Pada Pasien Kanker Nasofaring Di Rumah Sakit Kanker Dharmais Provinsi DKI Jakarta 2022 - Titi Sabariyah; Yuni Susilowati; Lastri Mei Winarni; Nurry Ayuningtyas (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Mucositis as one of the side effects of chemotherapy is inflammation that has toxic properties as a result of radiotherapy or chemotherapy which has an impact on disrupting the entire gastrointestinal system from oral to anal, the results of a preliminary study of data obtained on cases of mucositis in cancer patients in hospitals Dharmais Cancer from August to October 2022. Objective: To determine the effect of oral hygiene with 0.9% NaCl on reducing the grade of mucositis in nasopharyngeal cancer patients at Dharmais Hospital, Jakarta. Research method: Quasi experiment (quasi experiment), The quasi experimental design used was Pre and Post Test Without Control, The number of samples used was 17 people. Data analysis using t-test. Research results: The results of the analysis of differences in mucositis grades showed that before the oral hygiene intervention with 0.9% NaCl (pre-test) the average mucositis grade of respondents was 10.59 with a standard deviation of 2.181, but after the oral hygiene intervention was carried out with NaCl 0.9% (post-test) there was a change in the average mucositis grade to 9.53 with a standard deviation of 2.183. The statistical test results obtained a p value of 0.000, meaning that there was an effect of oral hygiene with 0.9% NaCl on reducing the grade of mucositis in nasopharyngeal cancer patients at the Dharmais Cancer Hospital, Jakarta. Conclusion: There is an effect of oral hygiene with 0.9% NaCl on reducing the grade of mucositis in nasopharyngeal cancer patients at Dharmais Cancer Hospital Jakarta, with a p value of 0.000 (<0.05).